SmartRegion: a region-based, distributed approach to software defined networks. (2016) - Moghaddam, Reza Farrahi; Lemieux, Yves; Cheriet, Mohamed
Redistribution of the intelligence and management in the software defined networks (SDNs) is a potential approach to address the bottlenecks of scalability and integrity of these networks. We propose to revisit the routing concept based on the notion of regions. Using basic and consistent definition of regions, a region-based packet routing framework called SmartRegion routing is presented. The flexibility of regions in terms of naming and addressing is then leveraged in the form of a region stack among other features placed in the associated packet header. In this way, most of complexity and dynamicity of a network is absorbed, and therefore, highly fast and simplified routing at the inter-region level along with semi-autonomous intra-region routing will be feasible. In addition, multipath planning can be naturally realised at both inter- and intra-levels. Simplicity, scalability, and manageability of the proposed approach would also bring future potentials to reduce energy consumption and environmental footprint associated to the SDNs. First, a basic form of SmartRegion routing mechanism is provided. Then, various applications, such as enabling seamless broadband access, providing beyond the internet protocol addressing mechanisms, and also address-equivalent naming mechanisms, are considered and discussed.